Anibal Quijano (1930-2018), Instituto de Estudos Avançados e o contexto peruano - Zevallos, Enrique Amayo (Instituto de Estudos Avançados da Universidade de São Paulo, 2018)
ABSTRACT The idea for this paper came to me when I sent an email to Carlos Gilherme Mota informing him that, sadly, Peruvian sociologist Anibal Quijano had passed away on May 5, 2018, in Lima. Carlos Guilherme was responsible for Anibal’s appointment as Visiting Professor at the Institute of Advanced Studies (IAS) of the University of Sao Paulo (USP). This paper intends to remember how Anibal came to the Institute, offer information on the Peruvian context during his career and point out some connections that he established with the academic milieu in São Paulo.

RESUMO A origem deste trabalho é um e-mail que encaminhei a Carlos Guilherme Mota informando, com tristeza, que o sociólogo peruano Aníbal Quijano havia falecido em Lima em 31 de maio de 2018. Graças a Carlos Guilherme, Aníbal passou um período como professor convidado do Instituto de Estudos Avançados (IEA) da Universidade de São Paulo. O objetivo deste trabalho é lembrar como chegou Aníbal ao IEA, fornecer alguma informação sobre o contexto peruano de sua formação, bem como assinalar alguns dos vínculos que então ele estabeleceu nos meios acadêmicos de São Paulo.
Keywords: Anibal Quijano; Institute of Advanced Studies (IAS) of the University of São Paulo (USP); Sociologist; Peru; Context; Aníbal Quijano; Instituto de Estudos Avançados da Universidade de São Paulo; Sociólogo; Peru; Contexto